NILAI PENDIDIKAN KARAKTER DALAM BUKU CERITA ANAK THE GOLDEN APPLE KARYA TERE LIYE - Mitra Esha (PT. CASA CENDEKIA MEDIA, 2024)
It cannot be ignored how important to instill character values from an early age to shape children’s personalities. Childhood is a crucial time for building ways of thinking and behaving, and the moral principles established during this period will form a strong foundation for their actions and attitudes in the future. The purpose of this study is to analyze the character values in the book The Golden Apple by Tere Liye. This research is qualitative using a descriptive method. The data analyzed are taken from The Golden Apple by Tere Liye, which contains character values. The technique used in this research involves reading and text analysis. This technique involves thorough reading and analysis of the book’s text to identify the character values contained within it. The focus is on the text, actions, and character portrayals in the book. The results of the data analysis through description have identified several character values in The Golden Apple by Tere Liye.